2019
DOI: 10.1051/e3sconf/201911600078
|View full text |Cite
|
Sign up to set email alerts
|

Purification of model biogas from toluene using deep eutectic solvents

Abstract: Biogas from landfills and wastewater treatment facilities typically contain a wide range of volatile organic compounds (VOCs), that can cause severe operational problems when biogas is used as fuel. Among the contaminants commonly occur aromatic compounds, i.e. benzene, ethylbenzene, toluene and xylenes (BTEX). In order to remove BTEX from biogas, different processes can be used. A promising process for VOCs removal is their absorption in deep eutectic solvents (DES). In this work, three DES: ([ChCl] U TEG [ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The studies presented in the literature are limited to the removal of inorganic compounds, i.e., H 2 O, CO 2 , H 2 S, and NH 3 from gaseous phases [35][36][37]. Only a few works refer to their use to remove volatile organic compounds from the gas phase [38,39].…”
Section: Vscsmentioning
confidence: 99%
“…The studies presented in the literature are limited to the removal of inorganic compounds, i.e., H 2 O, CO 2 , H 2 S, and NH 3 from gaseous phases [35][36][37]. Only a few works refer to their use to remove volatile organic compounds from the gas phase [38,39].…”
Section: Vscsmentioning
confidence: 99%
“…Moura 29 conducted relevant exploratory work in 2017, which verified that the absorption performance, in terms of absorption capacity and cycling performance, of quaternary ammonium salt DESs for toluene, acetaldehyde, and dichloromethane is comparable to that of imidazolium ILs and silicone oil. Słupek 30 proposed that the chlorinated choline-tetraethylene glycol 1:2 DES can effectively remove toluene impurities from biogas, and its dynamic absorption performance is higher than that of imidazolium ILs. Song et al 31 studied the absorption performance of hydrophobic DES tetraethylammonium chloride-oleic acid (1:3) for toluene.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, DESs have been applied to capture various acid gases 27 including CO 2 , 28 NO x , 29 SO 2 , 30 H 2 S, 31 and NH 3 , 32 because of their remarkable hydrogen‐bonding ability. Recently, Słupek et al 33 found that ChCl‐based DESs have superior absorption capacity compared to ILs and conventional organic solvents. Moura et al 34 demonstrated the affinity of DESs for toluene, acetaldehyde, and dichloromethane by measuring the gas–liquid partition coefficients and liquid‐phase absorption capacities.…”
Section: Introductionmentioning
confidence: 99%
“…25,26 Up to now, DESs have been applied to capture various acid gases 27 including CO 2 , 28 NOx, 29 SO 2 , 30 H 2 S, 31 and NH 3 , 32 because of their remarkable hydrogen-bonding ability. Recently, Słupek et al 33 found that ChCl-based DESs have superior absorption capacity compared to ILs and conventional organic solvents. Moura et al 34 In this work, we study the application of DESs as new VOC absorbents in capturing condensable cyclohexane gas from molecular level (e.g., absorption mechanism) to systematic scale (e.g., absorption performance analysis).…”
mentioning
confidence: 99%